Karakteristik Fisik dan Fisikokimia Ekado Ikan Gabus dan Ayam dengan Penambahan Kacang Tolo dan Jamur Tiram (Pleuretus Ostreatus) - Dwiki Rafi Irsandi; Ita Fatkhur Romadhoni; Andika Kuncoro Widagdo; Niken Purwidiani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Ekado in this research is an innovative product made from snakehead fish, chicken, cowpeas and oyster mushrooms. This Ekado product is made from a dominant propotion of snakedhead fish. This is caused by the lack of utilization of fish meat and equal distribution of fish consumption in Indonesia. The aims of this research are 1) to determine the results of sensory quality including shape, color, taste, aroma and texture, 2) to determine the nutritional content of snakehead fish and ekado chicken with the addition of cowpeas and oyster mushrooms, 3) to determine the selling price per package 250 grams. This research used a sensory quality method with a total of 37 panelists who were assisted with assessment observation sheets 1-5. The resulting data was processed using a single anova test followed by the Duncan test. To determine the nutritional content (carbohydrates, protein, fat, fiber and calcium) a laboratory examination is carried out. The research results show: 1) There is an influence of the proportion of snakehead fish and chicken on the shape and texture criteria. 2) The nutritional content of the product is Carbohydrate 26.40%, Protein 17.60%, Fat 3.60%, Fiber 2.21%, Calcium 81.05mg/100g. 3) It is known that the selling price of snakehead fish and ekado chicken with the addition of cowpeas and oyster mushrooms is IDR. 30,000 per 250 gram packaging.